Enhancing Students' Reading Comprehension through Realia-Based Activities - Risma Atikah; Wiwied Pratiwi; Dian Anggraini (English Teaching and Linguistics Journal (ETLiJ), 2026)
Reading comprehension was one of the most challenging skills for EFL learners, especially when dealing with descriptive texts that required strong vocabulary and visualization ability. This study investigated how realia-based activities improved this skill among eighth-grade students at MTs Ma'arif Roudlotut Tholibin, a boarding school in Metro, Lampung, where access to technology was limited. A total of 18 students from Class VIIIA participated in this research during the academic year 2025/2026. The study employed a Classroom Action Research design following the Kurt Lewin model, which was conducted in two cycles with three stages in each cycle: Planning, Action, and Observation and Reflection. Reading comprehension tests and observation sheets were used to collect the data, and the findings were verified through methodological triangulation. The results showed a significant improvement across both cycles. The class mean score increased from 62.56 in the pre-test to 70.22 after Cycle 1, and further improved to 76.33 after Cycle 2, exceeding the passing standard of 74. The percentage of students who achieved the passing score increased from 22.2 percent to 77.8 percent. In addition, student participation improved from 70 percent to 90 percent between cycles. These findings indicated that the use of real objects in the classroom was an effective and practical approach to improve students’ reading comprehension, particularly in educational settings with limited access to digital resources.